Quantitative evaluation of surface roughness and mass loss for different types of composite resins used for clear aligner attachments: an in vitro study - Alshammari, Rana R.; Alshihah, Nada; Aldweesh, Aljazi (Frontiers in Materials, 2025)
ObjectivesDue to a lack of thorough published research, orthodontists’ clinical preferences influence the choice of composite resin for clear aligner attachments. According to a recent study on bonded attachments, all evaluated composite resins showed notable volumetric loss during brushing and heat cycling; however, brand-specific variations were observed. Nevertheless, mass loss and surface roughness are not directly represented by roughness and weight measurements. Therefore, the aim of this research was to compare the surface roughness and mass loss of six types of composite resins.Materials and methodsNinety rectangular composite resin attachments (2 × 4 × 1 mm) were fabricated using three flowable composite resins (Tetric PowerFlow, Filtek™ Supreme Flowable Restorative, and Clearfil Majesty Flow) and three restorative composite resins (Tetric PowerFill, Filtek™ Supreme XTE Universal, and Estelite Sigma Quick). Surface roughness and mass were recorded at baseline (T1) and after intervention (T2), which included thermocycling, simulated brushing, and abrasive testing. A 3D optical microscope profilometer and an analytical balance were used for measurement. Paired t-tests, one-way ANOVA, and Bonferroni post hoc tests were used for statistical analysis.ResultsUsing paired t-tests, all tested composite resins showed a statistically significant increase in surface roughness and mass loss (p < 0.05), except for Tetric PowerFill, which showed no significant surface change (p = 0.238). This was reflected by a homogenous parallel line as an abrasive effect, without obvious irregularities. Post hoc comparisons of final roughness at T2 between groups revealed that Filtek™ Supreme XTE Universal exhibited the highest surface roughness and the greatest mass loss (2.4% of total weight).ConclusionTetric PowerFill demonstrated superior resistance to surface wear and mass degradation, making it the most suitable material among those tested for long-term use as clear aligner attachments. In contrast, Filtek™ Supreme XTE Universal was the least resistant, indicating a higher need for clinical monitoring and potential replacement.